PENGARUH AESTHETIC, ESCAPE, EXPLORATION DAN CONVENIENCE TERHADAP MALL SHOPPING BEHAVIOR DI ERA TREN BERBELANJA ONLINE - Novita Novita (Universitas Bunda Mulia, 2019)
Traditionally, mall developers have tried to attract consumers through store diversity and availability of products in one place (one-stop shopping concept). But now, consumer market is more segmented. To obtain customer loyalty, mall must be able to attract unique motives and experiential needs, not just offering a shopping place that provides complete items at attractive prices. This paper aims to answer a major challenges in the success of the mall to attract visitors on the online shopping trends. Data were collected using questionnaires to mall visitors in Jakarta. A sample of 380 was analyzed using Multiple Linear Regression. This study suggests that physical shopping centers must be create a new atmosphere to attract different segments. hopping malls must provide different concepts and create new experiences that consumers can’t get in online purchases. Keywords : aesthetic, exploration, escape, convenience, mall shopping behavior.